In the Mind's Eye : Julian Hochberg on the Perception of Pictures, Films, and the World. - Peterson, Mary A. (Oxford University Press, USA, 2007)
Author List. Introduction. Section I: Selected Papers of Julian Hochberg. 1. Hochberg, C.B. & Hochberg, J. (1952). Familiar size and the perception of depth. Journal of Psychology, 34, 107-114. 2. Hochberg, J. & McAlister, E. (1953). A quantitative approach to figural goodness. Journal of Experimental Psychology, 46, 361-364. 3. Hochberg, J. & Beck, J. (1954). Apparent spatial arrangement and perceived brightness. Journal of Experimental Psychology, 47, 263-266. 4. Hochberg, J. (1956). Perception: Toward the recovery of a definition. Psychological Review, 63, 400-405. 5. Hochberg, J. (1962).